Principals' supervisory behavior as perceived by themselves and their respective teachers in Quezon City high schools - Boonlee, Pichai 1940- ([Quezon City s.n.], 1974)
A survey of eight high schools in four districts identified desirable instructional supervisory behavior of high school principals as perceived by themselves as announcement of classroom visits, polite responses to the greeting of the class, and class observations for the improvement of instruction. The desirable administrative supervisory behavior are friendliness to teacher outside the school, close supervision of administrative activities or projects, and initiation and supervision of worthwhile non-instructional administrative projects. A principal's encouragement of professional growth and creativity among teachers and introduction of worthwhile projects for the improvement of instruction are perceived by the teachers to be desirable instructional supervisory behavior. The desirable administrative supervisory behavior are greeting teachers, friendliness to teachers outside the school and consideration and fairness in implementing teacher's privileges.
Thesis (M.Ed.)--University of the Philippines.
Keywords: School superintendents and principals; School supervision